Dunaliella salina microalgae oppose thioacetamide-induced hepatic fibrosis in rats. (2020) - El-Baz, Farouk K.; Salama, Abeer A.A.; Hussein, Rehab A.
Highlights: Dunaliella salina opposed the fibrotic effect of thioacetamide in rat liver. D. salina significantly reduced serum levels of ALT, AST, ALP and total bilirubin. D. salina revealed an elevation in GSH and a reduction in MDA in sera. D. salina caused fall in hepatic contents of α-SMA and collagen I to normal level. Scoring of fibrosis indicated that D. salina is an efficient hepatoprotective agent. Abstract: Several hepatic pathological conditions are correlated with the stimulation of hepatic stellate cells. This induces a cascade of events producing accretion of extracellular matrix components triggering fibrosis. Dunaliella salina, rich in carotenoids, was investigated for its potential antagonizing activity; functionally and structurally against thioacetamide (TAA) - induced hepatic fibrosis in rats. Adult male albino Wistar rats were treated with three dose levels of D. salina powder or extract (daily, p.o.); for 6 weeks, concomitantly with TAA injection. Serum levels of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), bilirubin and albumin were determined. Reduced glutathione (GSH), malondialdehyde (MDA), smooth muscle actin alpha (α-SMA) and collagen I hepatic contents were also estimated. Treatment with D. salina powder or extract caused a significant decline in serum levels of AST, ALT, ALP, bilirubin, MDA and hepatic contents of α-SMA and collagen I. Additionally, serum albumin and GSH hepatic content were highly elevated. Liver histopathological examination also indicated that D. salina reduced fibrosis, centrilobular necrosis, and inflammatory cell infiltration evoked by TAA. The results implied that D. salina exerts protective action against TAA-induced hepatic fibrosis in rats. The phytochemical investigation revealed high total carotenoid content prominently β-carotene (15.2 % of the algal extract) as well as unsaturated fatty acids as alpha-linolenic acid which accounts for the hepatoprotective activity.